Airborne fungal spores as a potential hazard for the vineyard workers – a case report from the Carpathian foothills - Magdalena Wójcik; Halyna Voloshchuk; Idalia Kasprzyk (Acta Agrobotanica, 2023)
Fungal spores often cause allergic diseases in people working outdoors, especially in agriculture. In the case of vineyard workers, the threat of mycotoxins is generally considered, and aerobiological monitoring focuses mainly on pathogenic fungi that cause diseases in grapes. The current requirement is to increase knowledge regarding the risk to vineyard workers coming from highly allergenic fungal spores such as Alternaria and Epicoccum . Aerobiological monitoring was conducted using the volumetric method. The relationships between meteorological parameters and airborne fungal concentrations were detected using Spearman’s correlation and a logistic regression model. It was found that this risk is significant and is particularly strong from July to September, when periods of high concentrations of Alternaria and Epicoccum spores overlap. High concentrations of spores are favoured by an increase in air temperature, sunshine duration, and low relative humidity. When the weather conditions are favourable for the release and dispersion of spores, their concentration exceeds the threshold to trigger allergic reactions in sufferers. Due to their high concentrations and cross-reactions of their allergens with other aeroallergens, airborne fungal spores may pose a health risk to allergy sufferers working in vineyards. For this reason, aerobiological monitoring is particularly important in agricultural workplace.